2017
DOI: 10.1038/srep45576
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Apolipoprotein A-V Predicts Long-term Survival in Chronic Hepatitis B Patients with Acute-on-Chronic Liver Failure

Abstract: Hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) is a life-threatening condition, and the lipid metabolism disorder is common in the development of this disease. This prospective observational study aimed to define the characteristics of plasma apolipoprotein A-V (apoA-V) in long-term outcome prediction of HBV-ACLF, and a total of 330 HBV-ACLF patients were included and followed for more than 12 months. In this cohort, the 4-week, 12-week, 24-week and 48-week cumulative mortality of HBV-ACLF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
3
4
0
Order By: Relevance
“…Our findings also revealed a significant positive correlation with between sdLDL and hepatic aminotransferases. This agrees with findings of previous studies that reported significant rise in AST and ALT in proportion to raised LDL and triglycerides levels in patients with HBV infection [13, [34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…Our findings also revealed a significant positive correlation with between sdLDL and hepatic aminotransferases. This agrees with findings of previous studies that reported significant rise in AST and ALT in proportion to raised LDL and triglycerides levels in patients with HBV infection [13, [34][35][36].…”
Section: Discussionsupporting
confidence: 93%
“…19 HDL and major apolipoproteins, apoAI and apoAII, were also reduced in patients suffering from cirrhosis or HCC due to chronic HBV infection. 17,19 The current study showed increased levels of TG, LDL and VLDL in the HBV infected patients compared to the control groups, and is consistent with findings reported by Nonogaki et al 20…”
Section: Discussionsupporting
confidence: 91%
“…19 HDL and major apolipoproteins, apoAI and apoAII, were also reduced in patients suffering from cirrhosis or HCC due to chronic HBV infection. 17,19 The current study showed increased levels of TG, LDL and VLDL in the HBV infected patients compared to the control groups, and is consistent with findings reported by Nonogaki et al 20 Elevated LDL is an indicator of increased risk to cardiovascular related complications. 21 The linear model from the statistical analysis suggested that 71% variation in CVDR can be explained by age, T. chol, TG, HDL and LDL.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, ApoA5 may act as an early predictor for remnant liver growth after preoperative portal vein embolization and liver surgery as plasma TG influences the process of liver regeneration and ApoA5 controls and determines TG levels [13]. In our previous study, we also found ApoA5 predicted the prognosis of hepatitis B virus-associated acute-on-chronic liver failure (HBV-ACLF) [14]. Except for the potential of predicting the outcomes of HBV-ACLF, we speculated that ApoA5 may also be a potential target for clinical intervention based on the fact that disorder of lipid metabolism can produce abundant toxic metabolites in the liver to induce and aggravate liver injury.…”
Section: Introductionmentioning
confidence: 99%